A Novel Technique for Identification of Wear Values at Different Lengths after Multiple Clinical Use of Different File Systems - Neslihan Yılmaz Çırakoğlu; Ersan Çiçek; Cevat Özarpa; Yağız Özbay; Olcay Özdemir (Medicina, 2022)
Introduction The purpose of this research is to assess the wearing of the rotary file system (Protaper Next) and reciprocating file systems (Reciproc Blue and WaveOne Gold) at different lengths using a novel technique after in vivo clinical use. Materials and Methods Twelve different unused samples from each brand were accepted as reference values. For three different brands, the diameters of the files were measured by taking 12 samples used once, 12 samples used twice, and 12 samples used three times. Images were taken with a USB Micron Microscope, and file diameters were measured by determining limit values with Autocad. Result Reciproc Blue system was the most worn at apical 1 mm, and WaveOne Gold system was the most worn at apical 3 mm. PTN system exhibited the least wearing at any length. Moreover, less wearing was observed in the rotation motion than in the reciprocating motion. Conclusion In clinical practice, for the guttapercha to be fully adapted to the apical construction prepared according to the determined WL, the file should not undergo any wearing and volume reduction. Wearing—especially in the apical parts of the file—causes less preparation, and this situation could lead to apically obturation failure.